Evaluating the Quality of Religious Moderation: A Case Study of Students in Public High Schools - Muhammad Ihsan Nashihin; Faisal Sundani Kamaludin; Syariful Syariful; Ahmad Faizudin (At-Tarbiyat, 2024)
The aim of this study is to assess the degree of religious moderation among high school students. There are many cases of intolerance and violence between students in South Jakarta, that require a solution in the form of an attitude of religious moderation. Religious moderation, within the Indonesian context, represents a balanced approach to religious practices and beliefs, promoting harmony within the pluralistic Indonesian society. It encompasses an individual's commitment to religious principles, interactions within a diverse community, and civic responsibilities. Religious moderation teaches to have attitudes and actions in middle proportion. This research employs a quantitative approach with a descriptive methodology. Data is primarily collected through a structured questionnaire. The study's population consists of high school seniors in South Jakarta, with a representative sample drawn from five schools in the region. The findings reveal an overall mean score of 81.38 on a 0-100 scale, indicating a "good" level of religious moderation. Examining specific indicators, the results are as follows: (1) National commitment scores 80.60, categorizing as "good"; (2) Tolerance scores 82.28, also falling within the "good" category; (3) Anti-violence records 76.92, indicating a "medium" level; and (4) Accommodation of local culture registers 85.73, signifying a "good" level of moderation. This research contributes to providing an overview to the government and schools about the quality of religious moderation among high school students, so that the government and schools can take strategic actions such as developing curriculum, learning strategies and teaching materials in an effort to improve the quality of religious moderation attitudes among students